Analisis pembelajaran fotosintesis berbasis augmented reality untuk mengurangi miskonsepsi siswa sekolah dasar - Desma Dzuriansyah; Moh Salimi; Suhartono Suhartono; Kartika Chrysti Suryandari (Universitas Pendidikan Indonesia, 2026)
Science learning, particularly on photosynthesis, in elementary schools still faces misconceptions due to the material's abstract nature and limited opportunities for direct observation. This study aims to analyze the learning process, the use of instructional media, student misconceptions, and the need for Augmented Reality (AR)-based media. A qualitative approach was employed through interviews, and data were analyzed using indicators of the learning process, media use, misconceptions, and learning needs. The findings show that teachers have implemented learning in accordance with lesson plans, using a scientific approach supported by images, posters, videos, teaching aids, and hands-on activities, thereby enhancing student participation and learning outcomes. However, misconceptions persist, particularly regarding the process and timing of photosynthesis. Teachers reported that conventional media are insufficient to explain abstract concepts effectively. All respondents emphasized the importance of AR-based media for visualizing photosynthesis in a concrete, interactive way. Therefore, implementing Assemblr Edu as an AR learning medium has the potential to enhance conceptual understanding in elementary schools.